Can sowing speed affect corn yield? - Filho, Aldir Carpes Marques [UNESP]; Ventura, Heitor Cardoso (Revista de Agricultura Neotropical, 2021)
In sowing operation, it is essential to control the factors that can affect the quality of seed and fertilizer deposition. These factors range from the correct choice of dosing mechanisms to machine regulation and operating speed control. The present research aimed to analyze the influence of sowing speed on the productive performance of the corn crop. The study was carried out at Fazenda São Geraldo, in the municipality of Boracéia, São Paulo. Four operating speeds 3, 5, 7 and 9 km h-1 were applied in a seeder, with a mechanical horizontal seed meter. The experimental design was carried out in strips. The results showed that sowing operational speed directly influences the final corn yield. There is a positive correlation between sowing speed and reduction in seedling emergence. The speed of 3.0 kmh-1 showed the best results for seed deposition and yield. The speeds of 5, 7 and 9 km h -1 presented a reduction of 14.8, 42.5 and 67.2 bags per hectare.
A velocidade de semeadura pode afetar a produtividade do milho?
Keywords: Mechanization; Plantability; Sowing technology; Zea mays